The Estimation of Production Function in Educational Hospitals of Kurdistan University of Medical Sciences (2007-2011) - S Rezaei; T Miraki; N Jahanmehr; F Gharibi (Tehran University of Medical Sciences, 2014)
Background: the using of economic tools such as production function is one of the ways to improving performance and efficient use of hospital resources. The aim of this study was the estimation of production function in educational hospitals of Kurdistan University of Medical Sciences during 2007- 2011. Material & Methods: the number of inpatient as dependent variable and the numbers of active beds, nurses, doctors and other staffs as explanatory variables was considered. These data For 12 of hospitals since 2007 to 2011 was collected by production form. Also with Eviews software version 6 and panel data, the production function of hospitals was estimated. Results: the elasticity and marginal of production for all variables explanatory was positive. The marginal of production for bed active, physician, nurse and other staff was 16.7, 54, 23.6 and 40.9 respectively. The total of input coefficient was equal 1.08 and the return to scale was increasing. Conclusion: according to the positive marginal of production for all variables explanatory, for improving of productivity and efficient use of hospital resources is suggested that the managers of hospitals in exposure to regular and irregular demand can be used elasticity of production.